Multicultural Da'wah and Interethnic Communication among Madurese and Tenggerese Communities in East Java, Indonesia - Nurhuda, Muhammad; Yuwafik, Muhammad Hamdan (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study examines multicultural da'wah and interethnic communication between the Madurese and Tenggerese in supporting the development of local wisdom in Malang Regency. The diversity of local wisdom includes culture, religion, race, language, tribe, tradition, and others. The method applied is qualitative research with a descriptive analysis approach. The results of this study are: 1). Multicultural da’wah communication between the two tribes shows interaction patterns that lead to cultural assimilation and acculturation, 2). Although they have different mother tongues (Madurese and Tenggerese), Indonesian functions as the main means of communication, 3). Local wisdom passed on by both tribes, such as the values ​​of cooperation, deliberation, and mutual respect, serve as a strong foundation for building harmonious relationships, 4). Community leaders and religion leaders from both tribes have an important role in helping communication and resolving disputes. In a culturally diverse society, wisdom and awareness of diversity are needed to respect existing differences. The development of a shared identity through multicultural da'wah communication is gradual as part of the Malang Regency community, where ethnic diversity is considered an asset, not an obstacle. This strengthens the sense of ownership and solidarity among a society with various cultures.